Heavy metal concentrations in four fish species from the Lagos lagoon and their human health implications - Adewale Adetutu; Peter Ifeoluwa Adegbola; Abiodun Bukunmi Aborisade (Heliyon, 2023)
Background: Lagos lagoon is constantly being polluted from industrial and human activities. Fishes from Lagos lagoon contribute significant percentages of fish consumption in the Lagos metropolises. Therefore, this study evaluated heavy metal concentrations in tissues of four fish species (Sarotherodon melanotheron, Chrysichthys nigrodigitatus, C. gariepinus, and Ethmalosa fimbriata) from Lagos lagoons and their human health implication. Concentrations of heavy metals and potential health hazard to consumers were evaluated with reference to Estimated Daily Intake (EDI), Target Hazard Quotient (THQ) and Cancer Risk (CR). Results: Concentration of the heavy metals in the fish tissues was below the maximum permissible limit in fish. Similarly, the. EDI of the heavy metals in all the tissues was below the recommended allowance whereas, the. THQ estimated for the heavy metals in the tissues of the fish were less than 1. Consumption of arsenic, nickel, and cadmium in the fish might however pose carcinogenic risk. Conclusions: Although, the measured heavy metal concentration were within permissible limits for human consumption, the calculated health risk values indicated that Arsenic, cadmium and nickel might pose significant health risks to consumers. Therefore, biomonitoring of heavy metal accumulation in tissues of fishes must be put into consideration by regulatory authority.